Take the 2-minute tour ×
Physics Stack Exchange is a question and answer site for active researchers, academics and students of physics. It's 100% free, no registration required.

I am puzzling about an exercise in the book "Electromagnetic Theory" by Ferraro (p.543).

An electron (mass $m$, charge $-e$) in a monopole magnetic field $\vec{B}\left(\vec{r}\right)=g\frac{\vec{r}}{r^3}$ has due to the Lorentz force $\vec{F}_L=-e\vec{v}\times\vec{B}$ the following equation of motion:

$$m\ddot{\vec{r}}=-\frac{eg}{r^3}\dot{\vec{r}}\times\vec{r}.$$

Since $\vec{J}=\vec{r}\times\vec{p}+eg\frac{\vec{r}}{r}$ is constant, the electron moves on the surface of a cone, which tip is in the origin at $\vec{r}=0$. Mathematically, $\vec{r}\cdot\vec{J}=egr=rJ\cos\vartheta$, thus the angle $\vartheta$ between $\vec{r}$ and $\vec{J}$ is constant.

Now I use spherical coordinates:

$$\vec{r}=r\mathbf{e}_{r} $$ $$\vec{v}=\dot{\vec{r}}=\dot{r}\mathbf{e}_{r}+r\dot{\vartheta}\mathbf{e}_{\vartheta}+r\dot{\varphi}\sin\vartheta\mathbf{e}_{\varphi}$$ $$\vec{a}=\ddot{\vec{r}}=\left(\ddot{r}-r\dot{\vartheta}^{2}-r\dot{\varphi}^{2}\sin^{2}\vartheta\right)\mathbf{e}_{r}+\left(2\dot{r}\dot{\vartheta}+r\ddot{\vartheta}-r\dot{\varphi}^{2}\sin\vartheta\cos\vartheta\right)\mathbf{e}_{\vartheta}+\left(2\dot{r}\dot{\varphi}\sin\vartheta+2r\dot{\vartheta}\dot{\varphi}\cos\vartheta+r\ddot{\varphi}\sin\vartheta\right)\mathbf{e}_{\varphi} $$

and obtain the following equations of motion (using $\dot{\vartheta}=0$):

$$\ddot{r}=r\dot{\varphi}^2\sin^2\vartheta \qquad(1)$$ $$r\dot{\varphi}^2\cos\vartheta=\frac{eg}{mr}\dot{\varphi} \qquad(2)$$ $$2\dot{r}\dot{\varphi}+r\ddot{\varphi}=0 \qquad(3)$$ with the boundary conditions: $$r\left(0\right)=r_0\qquad\varphi\left(0\right)=0.$$

In order to solve (1) for $r\left(t\right)$, one has to use the fact that the kinetic energy $\frac{1}{2}m\vec{v}^2$ is conserved. This holds due to the vector potential $\vec{A}=\frac{1}{2}\vec{B}\times\vec{r}=0$. Therefore, $$\vec{v}^2=\dot{r}^2+r^2\dot{\varphi}^2\sin^2\vartheta\equiv u^2=\text{const}$$

Using this in (1) one gets the simplified differential equation: $$r\ddot{r}=u^2-\dot{r}^2\qquad(4)$$

Does anyone know how to derive the following solution of (4)? $$r\left(t\right)=r_0\sqrt{1+\left(\frac{ut}{r_0}\right)^2}\qquad(5)$$

Solving (2) for $\dot{\varphi}$: $$\dot{\varphi}=\frac{eg}{mr^2\cos\vartheta}$$

and inserting (5) I obtain: $$\varphi\left(t\right)=\frac{eg}{mr_0u\cos\vartheta}\arctan{\frac{ut}{r_0}}.$$

Now the solutions says: $$r\left(\varphi\right)=\frac{r_0}{\cos\left(\varphi\sin\vartheta\right)}.$$

But I get something similar, but not equal: $$r\left(\varphi\right)=\frac{r_0}{\cos\left(\frac{mr_0u\cos\vartheta}{eg}\varphi\right)}.$$

Has anyone an idea where I could have done something wrong?

share|improve this question

1 Answer 1

up vote 2 down vote accepted

Actually, I don't have to use the conservation of the kinetic energy. With a slightly different procedure, one gets another simplified differential equation.

Inserting (2) in (1):

$$\ddot{r}=\frac{e^2 g^2 \tan^2\vartheta}{m^2} \frac{1}{r^3}$$

Now look at:

$$\frac{\text{d}}{\text{dt}}\dot{r}^2=2\dot{r}\ddot{r}=\frac{e^2 g^2 \tan^2\vartheta}{m^2} \frac{2\dot{r}}{r^3}=\frac{\text{d}}{\text{dt}}\left(\frac{e^2 g^2 \tan^2\vartheta}{m^2}\frac{-1}{r^2}\right)$$

Thus, a simpler differential equation is obtained ($C=\text{const}$):

$$\dot{r}^2=\frac{e^2 g^2 \tan^2\vartheta}{m^2}\frac{-1}{r^2}+C$$

and can be solved by separation of variables:

$$\text{dt}=\frac{r\text{ dr}}{\sqrt{Cr^2-\frac{e^2 g^2 \tan^2\vartheta}{m^2}}}$$

$$t=\frac{1}{C}\sqrt{Cr^2-\frac{e^2 g^2 \tan^2\vartheta}{m^2}}+t_0$$

With $t_0=0$ and $r\left(0\right)=r_0$:

$$r\left(t\right)=\sqrt{\frac{e^2 g^2 \tan^2\vartheta}{m^2r_0^2}t^2+r_0^2}$$

Now solving for $\varphi\left(t\right)$ from (2):

$$\dot{\varphi}=\frac{eg}{m\cos\vartheta}\frac{1}{r^2}$$

$$\text{d}\varphi=\frac{m\cos\vartheta r_0^2}{eg\sin^2\vartheta}\frac{\text{dt}}{t^2+\left(\frac{m r_0^2}{e g \tan\vartheta}\right)^2}$$

Using the arctangent integral:

$$\int\frac{\text{dt}}{t^2+b^2}=\frac{1}{b}\arctan\frac{t}{b}$$

and $\varphi\left(0\right)=0$, one obtains:

$$\varphi\left(t\right)=\frac{1}{\sin\vartheta}\arctan\frac{e g \tan\vartheta\ t}{m r_0^2} $$

Finally,

$$r\left(\varphi\right)=r_0 \sqrt{\tan^2\left(\sin\vartheta \varphi\right)+1}=\frac{r_0}{\cos\left(\sin\vartheta\varphi\right)}$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.